PENINGKATAN SKILL COMPUTATIONAL THINKING SISWA SMK MELALUI PENGENALAN ALGORITMA DAN PEMROGRAMAN PYTHON - Sasa Ani Arnomo; Abram Yunus Purba; Hendri Kremer (ASOSIASI IDEBAHASA KEPRI, 2026)
In today's digital era, computational thinking skills are a crucial competency that vocational high school students must possess to face the challenges of Industry 4.0. This Community Service (PKM) activity aims to improve students' logical, systematic, and analytical thinking skills at SMKS IT Darussalam Boarding School 01 through an introduction to algorithms and the Python programming language. The method of implementing this activity is carried out through three main stages: Socialization and introduction to basic algorithm concepts interactively, a practical Python programming workshop covering data structures, flow control, and simple functions, and mentoring in creating mini-projects based on programming logic. The results of this activity are expected to provide students with a deep understanding of how to solve complex problems through decomposition, pattern recognition, abstraction, and algorithm design. Through mastering the basics of Python, students are expected to not only be able to write code but also have a strong foundation in programming logic that can be implemented in various fields of information technology in the future.